2018
DOI: 10.2471/blt.18.208603
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C virus seroprevalence, Burkina Faso: a cross-sectional study

Abstract: ObjectiveTo estimate population-wide hepatitis B and C seroprevalence using dried blood spot samples acquired for human immunodeficiency virus (HIV) surveillance as part of the 2010–2011 Demographic and Health Survey in Burkina Faso.MethodsWe used the database acquired during the multistage, clustered, population-based survey, in which 15 377 participants completed questionnaires and provided dried blood spot samples for HIV testing. We extracted sociodemographic and geographic data including age, sex, ethnici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 29 publications
7
57
5
Order By: Relevance
“…The prevalence of anti-HCV in this study was 5.4% in mothers and 2.1% among children. Meda et al [16], found a similar prevalence 3.6%, Zeba et al [37], 4.4% among blood donors in 2013. This is indicative of a stagnant prevalence of hepatitis C infection in the country.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The prevalence of anti-HCV in this study was 5.4% in mothers and 2.1% among children. Meda et al [16], found a similar prevalence 3.6%, Zeba et al [37], 4.4% among blood donors in 2013. This is indicative of a stagnant prevalence of hepatitis C infection in the country.…”
Section: Discussionmentioning
confidence: 72%
“…Burkina Faso is defined as a high transmission zone with HBsAg prevalence between 8.0-20.0%, HBcAb between 70.0-95.0% [22,23]. Past studies have confirmed this assumption with HBsAg prevalence varying between 9.1 and 16.0% among adults with however data collected in the urban zone among specific populations including blood donors, pregnant women, HIV positive person, more likely to be at higher risk than the general population [3,16,24]. In this first study using a random sampling approach to assess all HBV infection seromarkers in rural Burkina Faso, a much lower HBsAg prevalence of 6.3% among adults mothers and 0.8% among children was reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The income disparities and the alcohol availability between the different regions could explain those differences [32]. From a public health perspective this region also have the highest prevalence of Hepatitis B and C [33]. The inhabitants of these regions seem to cumulate the hepatotoxic risk of Hepatitis and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%